‘No Man is an Island’: Effects of social seclusion on social dream content and REM sleep - Tuominen Jarno; Olkoniemi Henri; Revonsuo Antti; Valli Katja (Wiley, 2022)
Based on the Social Simulation Theory of dreaming (SST), we studied the effects ofvoluntary social seclusion on dream content and sleep structure. Speciﬁcally, we studiedthe Compensation Hypothesis, which predicts social dream contents to increase duringsocial seclusion, the Sociality Bias – a ratio between dream and wake interactions – and theStrengthening Hypothesis, which predicts an increase in familiar dream characters duringseclusion. Additionally, we assessed changes in the proportion of REM sleep. Sleep dataand dream reports from 18 participants were collected preceding (n = 94), during(n = 90) and after (n = 119) a seclusion retreat. Data were analysed using linear mixed-effects models. We failed to support the Compensation Hypothesis, with dreamsevidencing fewer social interactions during seclusion. The Strengthening Hypothesis wassupported, with more familiar characters present in seclusion dreams. Dream socialinteractions maintained the Sociality Bias even under seclusion. Additionally, REM sleepincreased during seclusion, coinciding with previous literature and tentatively supportingthe proposed attachment function for social REM sleep.